Solution of the Structural Optimization Problem of a Multiagent Approach Based Cutter Design - Anosov, V.L.; Bohdanova, L.M.; Kolodyazhnyi, V.M.; Litovka, V.D. (Проблеми машинобудування, 2019)
This article proposes a decision support system project to find the optimal milling cutter design. At the preliminary design stage, morphological analysis is used. It allows us to find and systematize all possible milling cutter structures with the necessary functional purpose. To automate the design formation process, an algorithm based on a resolution method is applied, with the algorithm using the logic of first-order predicates. An enumeration of possible states and assembly of a milling cutter structure from ready-made elements are carried out. Наведений проект системи підтримки прийняття рішень для пошуку оптимальної конструкції фрези. На стадії попереднього проектування використовується морфологічний аналіз. Він дозволяє знайти і систематизувати усі можливі структури фрези з необхідним функціональним призначенням. Для автоматизації процесу формування конструкції застосовується алгоритм, що ґрунтується на методі резолюцій, який використовує логіку предикатів першого порядку. Робиться перебір можливих станів і складання конструкції фрези з готових елементів. Приведен проект системы поддержки принятия решений для поиска оптимальной конструкции фрезы. На стадии предварительного проектирования используется морфологический анализ. Он позволяет найти и систематизировать все возможные структуры фрезы с необходимым функциональным назначением. Для автоматизации процесса формирования конструкции применяется алгоритм, основанный на методе резолюций, использующий логику предикатов первого порядка. Производится перебор возможных состояний и сборка конструкции фрезы из готовых элементов.